The Use of Vietnamese In Learning English As A Second Language - Vinh Phu Tran; Nhon Dang (TTU Review, 2021)
These years, the debate surrounding the role of the ﬁrst language (L1) in the second/foreign language (L2) classrooms in general and in English ones has been a controversial issue. On one hand, people support the idea that the inﬂuence of mother tongue should be excluded from second language acquisition. Meanwhile, the component of English-only method emphasizes the signiﬁcance from the use of L1 in English classes. This paper aims to investigate the positive inﬂuences of the use of Vietnamese in English learning process. From this point, two main things will be demonstrated. Firstly, using Vietnamese has a facilitating role to play in the classroom and can actually boost students’ learning. And secondly, there are good reasons for teachers and students to use Vietnamese to fully suit the context of speciﬁc lessons. To conduct this study, both quantitative and qualitative approaches were used. First of all, an online survey was conducted to collect realistic information from the students’ perspective. On the other hand, there were some in-depth interviews for teachers and tutors to express their experience as well as their own ideas about this issue. Finally, two separate classes were formally observed when they took a sample lesson which was taught in different methods. At the end of the course, a small test was provided to students to examine how much they understood their lesson. All the statistics and information received was analyzed, then mentioned in the paper.